Psychological mediators between risk perception and psychological wellbeing in emergency healthcare workers - Badía, Maria del Carmen; Alarcón, Rafael; Trillo, Javier; Miranda-Páez, Jesús (Frontiers in Psychology, 2024)
Healthcare workers are subject to numerous work-related stress factors that have negative consequences on their physical and mental health, making them a vulnerable group. The recent pandemic caused by the new coronavirus generated a high demand for attention from healthcare workers, putting their mental health at risk. The aim of this study is to test a mediation model in which Resilience and the satisfaction of psychological needs play a mediating role between Risk Perception, Attitude towards the management carried out by the administration and Emotional Intelligence on Psychological Well-being and depressive symptomatology of professionals who have been on the front line. The sample consisted of 405 healthcare professionals aged between 22 and 65 years, belonging to critical care units in southern Spain. Linear correlation and mediation analyses were performed. The results showed that psychological well-being showed positive correlations with resilience and negative correlations with discrepancy in the satisfaction of psychological needs. Depressive symptoms showed negative correlations with resilience and positive correlations with psychological need satisfaction. To explore these results further, a mediation analysis was conducted and a large set of significant indirect effects was found.